Studying Tumor Angiogenesis and Cancer Invasion in a Three‐Dimensional Vascularized Breast Cancer Micro‐Environment. Issue 7 (15th April 2021) - Dey, Madhuri; Ayan, Bugra; Yurieva, Marina; Unutmaz, Derya; Ozbolat, Ibrahim T.
Abstract: Metastatic breast cancer is one of the deadliest forms of malignancy, primarily driven by its characteristic micro‐environment comprising cancer cells interacting with stromal components. These interactions induce genetic and metabolic alterations creating a conducive environment for tumor growth. In this study, a physiologically relevant 3D vascularized breast cancer micro‐environment is developed comprising of metastatic MDA‐MB‐231 cells and human umbilical vein endothelial cells loaded in human dermal fibroblasts laden fibrin, representing the tumor stroma. The matrix, as well as stromal cell density, impacts the transcriptional profile of genes involved in tumor angiogenesis and cancer invasion, which are hallmarks of cancer. Cancer‐specific canonical pathways and activated upstream regulators are also identified by the differential gene expression signatures of these composite cultures. Additionally, a tumor‐associated vascular bed of capillaries is established exhibiting dilated vessel diameters, representative of in vivo tumor physiology. Further, employing aspiration‐assisted bioprinting, cancer–endothelial crosstalk, in the form of collective angiogenesis of tumor spheroids bioprinted at close proximity, is identified. Overall, this bottom–up approach of tumor micro‐environment fabrication provides an insight into the potential of in vitro tumor models and enables the identification of novel therapeutic targets as a preclinical drug screening platform. Abstract : A vascularized metastatic breast tumor model is fabricated depicting two important hallmarks of cancer, tumor angiogenesis, and cancer invasion. The role of matrix and stromal cell density on a tumor micro‐environment is demonstrated, and differentially expressed genes related to tumor development are highlighted. Further, aspiration‐assisted bioprinting of tumor spheroids reveals cancer–endothelial interaction in the form of collective angiogenesis.